2022
DOI: 10.1111/oik.08959
|View full text |Cite
|
Sign up to set email alerts
|

Direct and legacy‐mediated drought effects on plant performance are species‐specific and depend on soil community composition

Abstract: Droughts affect plant communities, but their impacts may be mediated by soil biota. Soil communities may ameliorate drought stress, and droughts may leave legacies of altered soil communities that may affect future plant growth. However, it is not yet understood which groups of soil biota in particular affect plant performance under drought, nor which groups contribute to drought‐legacy effects on future plant growth. We hypothesized that increasing soil‐community complexity ameliorates drought stress and that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Given that severe drought events are expected to increase as climate change advances (Pörtner et al 2022), understanding the effect of this extrinsic abiotic driver on PSF has become paramount. Drought leaves a strong signature in the soil, changing nutrient availability and stoichiometry (Gao et al 2020) and soil microorganism community composition (Canarini et al 2021;Meisner et al 2018), consequently influencing plant growth (Buchenau et al 2022). Such drought effects can have implications for ecosystem processes such as carbon cycling (Fuchslueger et al 2016).…”
Section: Drought and Floodingmentioning
confidence: 99%
“…Given that severe drought events are expected to increase as climate change advances (Pörtner et al 2022), understanding the effect of this extrinsic abiotic driver on PSF has become paramount. Drought leaves a strong signature in the soil, changing nutrient availability and stoichiometry (Gao et al 2020) and soil microorganism community composition (Canarini et al 2021;Meisner et al 2018), consequently influencing plant growth (Buchenau et al 2022). Such drought effects can have implications for ecosystem processes such as carbon cycling (Fuchslueger et al 2016).…”
Section: Drought and Floodingmentioning
confidence: 99%
“…A major driver of drought legacies in grasslands is related to drought‐induced changes in plant–soil feedbacks (PSFs), that is the interactions between plants, soil organisms, and abiotic soil factors, which lead to altered plant composition and performance and have cascading effects on ecosystem properties (Buchenau et al, 2022; Crawford & Hawkes, 2020; DeVries et al, 2019; Peguero et al, 2019; Preece & Peñuelas, 2016; Pugnaire et al, 2019; van der Putten et al, 2013; van der Putten et al, 2016; Williams & DeVries, 2020). Drought can influence PSFs e.g.…”
Section: Drought Legacies and The Underlying Mechanisms At Species Co...mentioning
confidence: 99%
“…It is well known that the high abundance of R. solani can severely damage their host plants 69,70 . A strong reduction of root biomass in our study during extreme drought could also have reduced the abundance of such endophytic fungi 71,72 , which subsequently promoted the performance of invading plants 73 . A recent study further suggested that fungal community responses to drought were closely related to root trait responses to soil water scarcity although pathogenic fungal responses were rather weak to drought 74 .…”
Section: Discussionmentioning
confidence: 71%
“…No reuse allowed without permission. subsequently promoted the performance of invading plants 73 . A recent study further suggested that fungal community responses to drought were closely related to root trait responses to soil water scarcity although pathogenic fungal responses were rather weak to drought 74 .…”
Section: Discussionmentioning
confidence: 99%